Impact of Chemotherapy on Extracellular Vesicles: Understanding the Chemo-EVs - Ab Razak, Nur' Syahada; Ab Mutalib, Nurul Syakima; Mohtar, M. Aiman; Abu, Nadiah (Frontiers in Oncology, 2019)
Chemotherapy is the standard go-to treatment for cancer besides surgery and radiation. It has recently come to light that the interaction between chemotherapy with the immune system is important in maintaining tumor immunity as well as influencing the efficacy of the therapy. However, ample preclinical studies have shown that in addition to direct cytotoxic effects on cancer cells, a fraction of chemotherapeutic agents may actually promote immunogenic cell death and alter the inflammatory milieu of the tumor microenvironment. Extracellular vesicles (EV) have been shown to interact with the tumor microenvironment and in the circulation by delivering alterative signals to these cells and interfere with their anti-tumor functions. Chemotherapy-induced extracellular vesicles (chemo-EVs) have been shown to carry different cargo loads than non-induced EVs. Aside from chemoresistance, there have been studies showing the effects of chemo-EVs on other tumor behaviors, especially in terms of metastasis, immune response and cancer stemness. Hence, this mini-review attempts to summarize and evaluate some of the reports on chemo-EVs involved in other types of tumor-related processes.